Procedure for Identifying Metaphorical Scenes (PIMS): The Case of Spatial and Abstract Relations. - Johansson Falck, Marlene; Okonski, Lacey (Metaphor & Symbol)
This article tackles the tricky problem of identifying metaphors in language that includes prepositions. We demonstrate how the Procedure for Identifying Metaphorical Scenes (PIMS) reflected and evoked by linguistic expressions in discourse, Johansson Falck & Okonski, accepted) can be used to identify metaphorical relations reflected in language. The scenes evoked correspond to conceptualizations that are directly attested by the specific linguistic constructions in the sentences under analysis. We present two studies that test the reliability of the procedure and the sensitivity of the tool for prepositions. Results show that PIMS provides a simple procedure that increases both reliability and sensitivity for prepositional constructions. By focusing on the scenes evoked by linguistic constructions, the procedure highlights the contextual meanings of the constructions and the specific experiences that they code.